2021
DOI: 10.1111/ijsa.12334
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback on interview self‐efficacy and outcome expectations

Abstract: Employment interview still gathers elevated scholarly attention, as it represents the most popular selection tool among employers (Macan, 2009;McCarthy & Cheng, 2018), and it is seen favorably by applicants (Anderson et al., 2010). Scholars have been increasingly studying the employment interview from the applicants' perspective (McCharty & Cheng, 2014), focusing on their attitudes, self-cognitions, and emotions, and evaluating the impact of these aspects on their performance (see Nikolaou & Georgiou, 2018;Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Huffcutt, 2011). Moreover, aligning with CSM, research has also shown that those with firmer ISE beliefs have better outcome expectations about the job interview (Petruzziello et al, 2021). Stated differently, those who believe themselves to be better performers in a job interview think this bodes well for succeeding in future job interviews (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
See 1 more Smart Citation
“…Huffcutt, 2011). Moreover, aligning with CSM, research has also shown that those with firmer ISE beliefs have better outcome expectations about the job interview (Petruzziello et al, 2021). Stated differently, those who believe themselves to be better performers in a job interview think this bodes well for succeeding in future job interviews (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…vicarious learning, Liu et al, 2014) and giving formative feedback about one's interviewing capability (i.e. verbal persuasion and encouragement; Petruzziello et al, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%